2012
DOI: 10.1515/crelle-2012-0053
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence, orbit equivalence, and the classification of nuclear C* -algebras

Abstract: Abstract. We bound the Borel cardinality of the isomorphism relation for nuclear simple separable C * -algebras: It is turbulent, yet Borel reducible to the action of the automorphism group of the Cuntz algebra O2 on its closed subsets. The same bounds are obtained for affine homeomorphism of metrizable Choquet simplexes. As a by-product we recover a result of Kechris and Solecki, namely, that homeomorphism of compacta in the Hilbert cube is Borel reducible to a Polish group action. These results depend intima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…We record a consequence on the classification problem for strongly selfabsorbing algebras (see [17] for the definitions). While the isomorphism relation for separable C * -algebras (and even separable AI algebras) is not classifiable by countable structures ( [18]), our result shows that the isomorphism relation for strongly self-absorbing algebras is much simpler. Since the computation of a theory of a C * -algebra is given by a Borel function ( [17]) the following is an immediate consequence of Theorem 2.16.…”
Section: 4mentioning
confidence: 73%
“…We record a consequence on the classification problem for strongly selfabsorbing algebras (see [17] for the definitions). While the isomorphism relation for separable C * -algebras (and even separable AI algebras) is not classifiable by countable structures ( [18]), our result shows that the isomorphism relation for strongly self-absorbing algebras is much simpler. Since the computation of a theory of a C * -algebra is given by a Borel function ( [17]) the following is an immediate consequence of Theorem 2.16.…”
Section: 4mentioning
confidence: 73%
“…This framework captures the vast majority of concrete classification results in mathematics. (In [11] and [12] the computation of most of the invariants in the theory of C*-algebras is shown to be Borel. )…”
Section: Introductionmentioning
confidence: 99%
“…Many nonclassifiability results were established directly or indirectly using this criterion. For instance Hjorth showed in [17] (Section 4.3) that the orbit equivalence relation of a turbulent Polish group action is Borel reducible to the relation of homeomorphism of compact spaces, which in turn is reducible to the relation of isomorphism of separable simple nuclear unital C*-algebras by a result of Farah-Toms-Törnquist (Corollary 5.2 of [11]). As a consequence these equivalence relations are not classifiable by countable structures.…”
Section: Introductionmentioning
confidence: 99%
“…Let K Choq denote the convex subsets of Q that are Choquet simplexes. In Section 4 of [FTT14], it is shown that K Choq is a Borel subset of K(Q), and may be taken to be the standard Borel space of metrizable Choquet simplexes. In [Sab13], Sabok shows that E grp ∼ B ≈ a , the relation of affine homeomorphism on K Choq .…”
Section: Homeomorphism Of Compact Metric Spacesmentioning
confidence: 99%
“…Later, J. Melleray in [Mel07] demonstrated that the classification of separable Banach spaces by linear isometries is also complete in this class. More recently, in [FTT14] and [EFP + 13], the isomorphism relation on separable C*-algebras was seen to be a member of this family as well, and it too was proven to be complete in [Sab13].…”
Section: Introductionmentioning
confidence: 99%